Words and their stories : essays on the language of the Chinese revolution - Wang, Ban, 1957- (Handbuch der Orientalistik. China ;, 2011)
As China joins the capitalist world economy, the problems of social disintegration that gave rise to the earlier revolutionary social movements are becoming pressing. Instead of viewing the Chinese Revolution as an academic study, these essays suggest that the motifs of the Revolution are still alive and relevant. The slogan ""Farewell to Revolution"" that obscures the revolutionary language is premature. In spite of dislocations and ruptures in the revolutionary language, to rethink this discourse is to revisit a history in terms of sedimented layers of linguistic meanings and political aspir.